Association of Plasma Calprotectin Levels with Disease Severity in COVID-19 Patients - Sincan, Suat; Sincan, Gülden; Kızıltunç, Ahmet (Ibnosina Journal of Medicine and Biomedical Sciences, 2025)
Inflammation plays an important role in the pathogenesis of COVID-19. Calprotectin, a protein released by inflammatory cells, is associated with this inflammatory response.A prospective study was conducted on 30 patients with mild to moderate COVID-19, 30 patients with severe COVID-19, and 30 healthy controls. Calprotectin levels were analyzed with a commercially purchased Cloud Cloning Kit.Plasma calprotectin levels in COVID-19 patients (12.5 ± 8.8 ng/mL) were significantly greater than those in the controls (8.23 ± 2.99 ng/mL; p = 0.012). The calprotectin level in the mild to moderate COVID-19 group (9.85 ± 6.94 ng/mL) was significantly lower than that in the severe COVID-19 group (15.19 ± 9.87 ng/mL; p = 0.019). The recommended cutoff value for the calprotectin level was 7.45 ng/mL with 63.3% sensitivity and 53.3% specificity. Seventeen (28.3%) of the COVID-19 patients died due to COVID-19-related causes. The calprotectin level in the exiting patients (16.33 ± 7.65 ng/mL) was significantly greater than the calprotectin level in the living cases (11.01 ± 8.95 ng/mL; p = 0.035).Calprotectin levels were greater in COVID-19 patients than in healthy controls and in more severe patients than in mild to moderate cases. Calprotectin levels may be used as a biomarker to predict severe COVID-19 cases.
Keywords: COVID-19; calprotectin; prognosis; biomarker; severity